LEXICLIMB: USING DIGITAL BOARD GAME TO ENHANCE VOCABULARY ACQUISITION AMONG YEAR 4 PUPILS IN ESL CLASSROOM - Nur Amirah Mohd Yazid; Azlina Abdul Aziz (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
This research aims to investigate the effectiveness of LexiClimb, a digital board game adapted from Snake and Ladder and Scrabble, in enhancing vocabulary acquisition among 60 Year 4 pupils in a primary school in Kuala Lumpur, Malaysia. LexiClimb integrates interactive gameplay with instructional material, necessitating learners to accomplish vocabulary quests and challenges as they progress in the game. This research applied a mixed-method research design and data were collected through pre- and post-tests, pupil questionnaires, teacher feedback forms, reflective journals, and semi-structured interviews. The quantitative analysis showed that LexiClimb improved vocabulary acquisition from 13.3 to 22.1, demonstrating its potential as an engaging and effective learning aid. Qualitative data showed that pupils found the game motivating, engaging, fun, and interactive, with competitive features boosting intrinsic and extrinsic motivation. Teachers’ observations showed improved language recall, engagement, and classroom interaction. The findings support theories of behaviourism, social constructivism, and game-based learning, indicating that LexiClimb’s gamified design, characterized by repetition, immediate feedback, and collaboration, facilitates effective vocabulary acquisition. The tool’s accessibility and adaptability render it a valuable resource for overcoming challenges in traditional ESL vocabulary instruction. The implications indicate wider applications of LexiClimb in grammar instruction or with the lower primary pupils, underscoring its potential as a transformative digital resource for ESL classroom learning.